ANALISIS PERMASALAHAN PENGADAAN INFRASTRUKTUR TI INSTANSI PEMERINTAH: PENGALAMAN DARI PENDAMPINGAN BPKP - Harahap, Rudy M (Bina Nusantara University, 2007)
Considering on the amount of money expenses, the Procurement of government IT Infrastucture is significantlyincreased. But, the increased of IT infrastructure expenses has not been supported by a good procurement process.Whereas, procurement process of IT infrastructure is one of IT governance parts, that is a system realization processaccording to Panduan Umum Tata Kelola Teknologi Informasi dan Komunikasi Nasional that published by Communicationand Information Ministry. Article discusses problem analysis on the procurement of government IT infrastructure. Theproblem analysis refer to framework ideal process of procurement of IT infrastructure that published by Cluster Consultant.From the framework, some problems are found on the whole level process of procurement of government IT infrastructurethat needs to be fixed.Keywords: procurement, infrastructure, information technology, governance